An Analysis of Kerima Polotan - Tuvera's short stories using the transitivity system - Lacandola, Imelda S.; Arcellana, Lydia R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2003)
This study deals with the fiction of Kerima Polotan Tuvera in which the main concern is to analayze how she portrays her female characters in juxtaposition with the male ones in the short stories. The study utilizes M.A.K. Halliday's transitivity system, which falls under ideational function of the Systemic Functional Grammar. It is the study's contention that using the said system will provide a solid linguistic basis for the analysis of the female characters portrayed in the short stories. Four short stories are selected to form the material of the study and these are The Virgin, Cost Price, The Sounds of Sunday and A Various Reason. From these stories, specific excerpts are chosen, and broken down to clauses to provide units for analysis. These clauses are isolated and subjected to functional labeling. This is carried out to provide a means of interpreting grammatical structures, which, later on, becomes the bases for any semantic interpretations. A tabulation for the six processes is presented that help lead to the description of the main characters in the four short stories. This study has proven that through Halliday's framework, it it possible to uncover linguistic features that could aid in the reader's understanding of a literary work.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.